2018
DOI: 10.1101/267849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell atlas of human uterus

Abstract: The human uterus is a highly dynamic tissue that undergoes repeated damage repair and regeneration during the menstrual cycle, which make it ideal model to study tissue regeneration and pathological process. Stem/progenitors were speculated to be involved in the regeneration of endometrial epithelial and pathogenesis of endometriosis. But the identity, microenvironment and regulatory mechanisms of the uterus epithelial stem/progenitors in vivo remain unclear. Here, we dissected the cell heterogeneities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In humans, such cells are commonly thought to be located in the basalis segment of the endometrial glands ( Nguyen et al, 2012 ; Patterson and Pru, 2013 ; Valentijn et al, 2013 ). However, according to a recent single-cell transcriptome study of secretory-phase human endometrium, cells showing characteristics of stem/progenitor cells are located in the upper region of the functionalis ( Wu et al, 2018 preprint). At the same time, several studies have suggested that endometrial epithelium can be regenerated by stem cells of either stromal/mesenchymal ( Huang et al, 2012 ; Patterson et al, 2013 ) or bone marrow cell origin ( Bratincsak et al, 2007 ; Du and Taylor, 2007 ; Ikoma et al, 2009 ; Mints et al, 2008 ; Taylor, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, such cells are commonly thought to be located in the basalis segment of the endometrial glands ( Nguyen et al, 2012 ; Patterson and Pru, 2013 ; Valentijn et al, 2013 ). However, according to a recent single-cell transcriptome study of secretory-phase human endometrium, cells showing characteristics of stem/progenitor cells are located in the upper region of the functionalis ( Wu et al, 2018 preprint). At the same time, several studies have suggested that endometrial epithelium can be regenerated by stem cells of either stromal/mesenchymal ( Huang et al, 2012 ; Patterson et al, 2013 ) or bone marrow cell origin ( Bratincsak et al, 2007 ; Du and Taylor, 2007 ; Ikoma et al, 2009 ; Mints et al, 2008 ; Taylor, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the source of cells that infiltrate the lung has remained elusive, however, as have the mechanisms of tumorigenesis, metastasis, invasion, and cystic remodeling Krymskaya and McCormack, 2017;McCormack et al, 2012). In the present study, scRNA-seq analysis of LAM lesions identified unique, non-pulmonary mesenchymal cells, which we termed LAM CORE cells, that share a high degree of transcriptomic similarity to the LAM CORE cells in uterus of an S-LAM patient and with myometrial and stromal cells (express high level of MME, FN1, COL3A1, HOXA10) from normal human and mouse uteri (Mucenski et al, 2019;Wu et al, 2018) . A prominent neural crest signature was also identified in pulmonary and uterine LAM CORE cells and in normal uterus.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, uterine myocyte, epithelial, immune, endothelial and several stromal cell subtypes were identified (Figure 6a; Figure S15). Endometrial epithelia (expressing high level of KRT8, KRT18, EPCAM, CLDN3) and stromal cells (expressing high level of MME, FN1, COL3A1, HOXA10, VIM ) were defined based on the gene markers from the human and mouse uterus altas (Mucenski et al, 2019;Wu et al, 2018) . Hierarchical clustering of major cell types from LAM lung and LAM uterus demonstrated close correlation of LAM CORE cells from both tissues (Figure 6b).…”
Section: Identification Of Lam Core Cells In Uterus From a Patient Wimentioning
confidence: 99%
“…The widespread adoption of single-cell transcriptomics has led to a growing body of “atlas” datasets describing tissue heterogeneity with unprecedented resolution 1 . As atlas data across species 2 , tissues 3 7 , development 8 10 , and aging 4 , 11 are being amassed, a number of algorithms have been proposed to compare new data against reference data sets. The basic concept behind these efforts is to emulate the Basic Local Alignment Search Tool (BLAST) for nucleic acid and protein sequence matching 12 , except in gene expression space.…”
Section: Introductionmentioning
confidence: 99%